Game Theory - Peters, Hans (Springer, 2017)
This book is a compilation of much of the material I used for various game theory coursesover,roughly,thepasttwodecades.Theﬁrstpart,ThinkingStrategically,is intendedforundergraduatestudentsin economicsor business, butcan also serveas an introductionfor the subsequentparts of the book. The second and third parts go deeper into the various topics treated in the ﬁrst part. These parts are intended for more mathematically oriented undergraduate students, or for graduate students in (for instance) economics. Part II is on noncooperativegames and Part III on cooperative games. Part IV is only a mathematical tools chapter. Every chapter has a ﬁnal section with problems. Selected hints, answers, and solutions to these problems are givenat the end of the book.Complete solutions can be obtainedfrom the author. The book claims neither originality nor completeness. As to originality, the material draws heavily on game theory texts developed by many others, often in collaboration. I mention in particular Jean Derks, Thijs Jansen, Andr´es Perea, Ton Storcken,FrankThuijsman,Stef Tijs, DriesVermeulen,andKoosVrieze.Iam also greatlyindebtedtoalargenumberofintroductory,intermediate,andadvancedtexts andtextbooksongametheory,andhopeI havesucceededin givingsufﬁcientcredit to the authorsof these works in all relevantplaces. As to completeness,the bookis far from achievingthis quality but I trust that it presents at least the basics of game theory. When writing and compiling the material I had ambitious plans for many more chapters, and only hope that the phrase that all good things must come to an endapplieshere.